Towards Indigenous Cosmopolitanism / Vers un cosmopolitisme bolivien - Politano, Candida (Glendon Journal of International Studies, 2013)
Abstract: This research paper aims to examine the contemporary politicization of Bolivia’s indigenous identified peoples through the lens of indigenous cosmopolitanism (Goodale 2006). By applying this hybrid theory of cosmopolitanism we can better understand the possibility of plurinational forms of governance and citizenship in the country. Using Mark Goodale’s theory we can begin to piece together indigenous cosmopolitanism in its capacity to combine indigeneity with other more global forms of inclusion. Indigenous civil society has envisioned a new type of sociopolitical citizenship, a new framework of belonging in which marginalized indigenous groups are brought together with other members of “the race”. To understand the way in which this indigenous cosmopolitanism has affected Bolivian politics and society this paper will look to examine the current party in power, Movimiento al Socialismo (MAS), the Bolivian Constitution of 2009 and the El Alto region’s Wayna Rap Movement. Résumé: Cet article vise à examiner la politisation actuelle des peuples identifiés comme indigènes en Bolivie à travers le prisme du cosmopolitisme indigène (Goodale 2006). Par l’application de cette théorie hybride du cosmopolitisme, nous pouvons mieux comprendre la possibilité de formes plurinationales de gouvernance et de citoyenneté dans le pays. En utilisant la théorie de Mark Goodale, nous pouvons commencer à reconstituer le cosmopolitisme indigène dans sa capacité à combiner indigénéité avec d’autres formes plus globales d’inclusion. La société civile indigène a envisagé un nouveau type de citoyenneté sociopolitique, un nouveau cadre d’appartenance dans lequel les groupes marginalisés indigènes sont réunis avec les autres membres de «la race». Afin de comprendre la manière dont ce cosmopolitisme indigène a affecté la politique et la société boliviennes, ce article examinera l’actuel parti au pouvoir, Movimiento al Socialismo (MAS), la Constitution bolivienne de 2009 et le mouvement rap Wayna de la région d’El Alto.